The analysis of immunogenic cell death induced by ablation at different temperatures in hepatocellular carcinoma cells - Wang, Mengdong; Duan, Yaxin; Yang, Mao; Guo, Yongfei; Li, Fengtan; Wang, Junping; Si, Tongguo (Frontiers in Cell and Developmental Biology, 2023)
Introduction: Ablation therapy is a commonly used tool in the management of hepatocellular carcinoma (HCC). After ablation, dying cancer cells release a variety of substances that trigger subsequent immune responses. Immunogenic cell death (ICD) has been a trending topic in recent years and has been discussed many times along with oncologic chemotherapy. However, the subject of ablative therapy and ICDs has been little discussed. The purpose of this study was to investigate whether ablation treatment induces ICD in HCC cells and whether different types of ICDs arise because of different ablation temperatures. Methods: Four different HCC cell lines (H22, Hepa-16, HepG2 and SMMC7221) were cultured and treated under different temperatures (−80°C, −40°C, 0°C, 37°C, and 60°C). Cell Counting Kit-8 assay was performed to analyze the viability of different cell lines. Apoptosis was detected by flow cytometry assay, and a few ICD-related cytokines (calreticulin, ATP, high mobility group box 1, and CXCL10) were detected by immunofluorescence or enzyme-linked immunosorbent assay. Results: The apoptosis rate of all kinds of cells increased significantly in −80°C group (p < 0.01) and 60°C group (p < 0.01). The expression levels of ICD-related cytokines were mostly significantly different between the different groups. For calreticulin, Hepa1-6 cells and SMMC7221 cells showed significantly higher protein expression levels in 60°C group (p < 0.01) and significantly lower protein expression levels −80°C group (p < 0.01). The ATP, high mobility group box 1 and CXCL10 expression levels were significantly higher in 60°C, −80°C and −40°C group of all four cell lines (p < 0.01). Conclusion: Different ablative treatments could induce different types of ICDs in HCC cells, providing a promising track for the development of individualized cancer therapies.